Lyrical prose in historical and theoretical coverage (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
A lot of literary studies are devoted to lyrical prose issues, but for the time being there is no full scientific vision of the problem with relating the phenomenon of lyrical prose and poetic prose. This is what causes the relevance of the topic, with its underlying desire to investigate the origin and evolution of lyrical prose as the artistic and aesthetic phenomenon, as well as the need to examine its stylistic and genre transformations, connection with the poetic prose. The proposed issues need to be clarified not only in terms of the theory, but also within the boundaries of literary history.
Keywords: lyrical prose; poetic prose; style; genre; literary race; epic; lyric; drama